PETROCHEMICAL SYSTEMATICS OF AMPHIBOLITES FROM THE ARCHEAN SECTION OF THE KOLA SUPERDEEP BOREHOLE - Kozlov N.E.; Martynov E.V.; Kozlova N.E.; Kaulina T.V.; Smirnov Yu.P. (My University, 2007)
This paper addresses the problem of the systematization of amphibolites from the Archean part of the section of the SG-3 Kola Superdeep Borehole. It was shown that a combined petrochemical and geochemical approach allows one to classify these rocks with high confidence and to distinguish supposedly Archean and Proterozoic varieties among them. It was found that Proterozoic rocks account for about 50–70% of basic rocks in the Archean section. Homologues of the basic metavolcanics of the Matert Formation were detected among the Proterozoic metaigneous rocks of the Archean section of the SG-3, which casts doubt on the conclusion of some authors on the allochthonous origin of the upper levels of the northern Pechenga section, including its productive horizons. This result has very important metallogenic implications.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей